On Everything Is Necessarily What It Is - Alex Blum (Organon F, 2023)
It is argued that if everything is necessarily what it is, then given the equivalence ‘p ≡ [a = (℩x)(x = a & p)]’, it follows that whatever happens or is the case, had to happen or had to be the case.